Preparation of biocompatible and photostable PEGylated red fluorescent nanoparticles for cellular imaging1. Issue 32 (28th August 2015) - Wang, Ke; Zhang, Xiaoyong; Zhang, Xiqi; Fan, Xingliang; Huang, Zengfang; Chen, Yi; Wei, Yen
<x xml:space="preserve">Abstract</x> Biocompatible and photostable PEGylated red fluorescent nanoparticles were prepared via surface-initiated ATRP and their cellular imaging application was successfully demonstrated.